The performance of marketplace lenders: Evidence from lending club payment data - Roman Kräussl; Zsofia Kräussl; Joshua Pollet; Kalle Rinne (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
Direct financing of consumer credit by individual investors or non-bank institutions through an implementation of marketplace lending is a relatively new phenomenon in financial markets. The emergence of online platforms has made this type of financial intermediation widely available. This paper analyzes the performance of marketplace lending using proprietary cash flow data for each individual loan from the largest platform, Lending Club. While individual loan characteristics would be important for amateur investors holding a few loans, sophisticated lenders, including institutional investors, usually form broad portfolios to benefit from diversification. We find high risk-adjusted performance of approximately 40 basis points per month for these basic loan portfolios. This abnormal performance indicates that Lending Club, and similar marketplace lenders, are likely to attract capital to finance a growing share of the consumer credit market. In the absence of a competitive response from traditional credit providers, these loans lower costs to the ultimate borrowers and increase returns for the ultimate lenders.
urn:nbn:de:hebis:30:3-469928
Keywords: G12; G21; 330; marketplace lending; peer-to-peer; portfolio performance; household finance; financial innovation; finance and technology